2019
DOI: 10.1097/md.0000000000014497
|View full text |Cite
|
Sign up to set email alerts
|

The term “floating” used in traumatic orthopedics

Abstract: Background: The term “floating” is used in orthopedic literature to describe certain patterns of skeletal injuries that share one common character which is disruption and discontinuity of bones above and below a joint. The first time used in orthopedic literature being in late 1970 to describe a type of elbow injury. Later the word was used increasingly and applied to a variety of injuries affecting the knee, shoulder, hip, forearm, hand, and ankle. Currently, there are about 12 different skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 92 publications
0
15
0
6
Order By: Relevance
“…In addition, they found a high rate of postoperative complications: iatrogenic injury of the sciatic nerve (24%) 2 Case Reports in Orthopedics and shortening of the femur (21%). Although there is no consensus on management of the floating hip, most authors agree on early stabilization of unstable pelvic injuries as a measure of adequate resuscitation according to the principles of damage control orthopedics [7,8]. We believe that the surgical order has to be discussed case to case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they found a high rate of postoperative complications: iatrogenic injury of the sciatic nerve (24%) 2 Case Reports in Orthopedics and shortening of the femur (21%). Although there is no consensus on management of the floating hip, most authors agree on early stabilization of unstable pelvic injuries as a measure of adequate resuscitation according to the principles of damage control orthopedics [7,8]. We believe that the surgical order has to be discussed case to case.…”
Section: Discussionmentioning
confidence: 99%
“…The latter depends on different parameters: fracture pattern, soft tissue trauma, patient's general condition, and surgeon preference. Several authors [8][9][10] recommended intramedullary nailing of the femur and the tibia that allows prompt mobilization, permits early weight-bearing, and prevents knee stiffness. It has been reported that the use of retrograde femoral nail permits to stabilize both fractures with a single incision [9,13] and reduces surgery time with less blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, single case reports and small case series (consisting mostly of two cases; except for Sanders et al case series study) have been recorded [2,[6][7][8]. To our knowledge, more than 40 cases in total have been reported since the early 1980s, making us question the rarity of the injury [1,2,9].…”
Section: Introductionmentioning
confidence: 93%
“…The floating clavicle is considered to be a rare entity [1,2,[6][7][8][9][10]. We present a misdiagnosed case of a 65-year-old male who underwent a motorcycle accident and was surgically treated six months post-injury.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation